Monkeypox Virus and Other Emerging Outbreaks: An Overview and Future Perspective - Amatul Hadi Hamdana MBBS; Habiba Mohsin MBBS; Zoaib Habib Tharwani MBBS; Waniyah Masood MBBS; Amatul Quddus Furqana MBBS; Affan Sohail MBBS; Amatul Rehman Durdana MBBS; Muhammad Talal Ashraf MBBS; Naseer Uddin MBBS; Zarmina Islam MBBS; Mohammad Yasir Essar DMD; Roy Rillera Marzo MPH, MBA; et al. (SAGE Publishing, 2023)
Monkeypox (MPX) is a zoonotic disease caused by the MPX virus from the poxviridae family of orthopoxviruses. Typically, endemic in central and west Africa, it has now become a matter of concern since cases have been reported in non-endemic countries around mid-June 2022, especially in the European region, with the transmission not related to travel. The diagnosis is made by PCR testing of the skin lesions. Even though treatment is symptomatic, antiretrovirals, such as tecovirimat, are used in severe cases. Vaccination with second and third generation vaccines is approved for prophylaxis in high risk individuals. Unfortunately, these options of treatment and prevention are only available in high income countries at the moment. This review, through a thorough literature search of articles from 2017 onward, focuses on epidemiology, clinical manifestations, challenges, treatment, prevention and control of MPX virus and how they can be corelated with other viral outbreaks including COVID-19, Acute Hepatitis of unknown origin, Measles and Dengue, to better predict and therefore prevent its transmission. The previous COVID-19 pandemic increased the disease burden on healthcare infrastructure of low-middle income countries, therefore, this recent MPX outbreak calls for a joint effort from healthcare authorities, political figures, and NGOs to combat the disease and prevent its further spread not only in high income but also in middle- and low-income countries.